A novel homozygous mutation in ATP13A2 gene causing pure hereditary spastic paraplegia. (May 2021) - Ban, Rui; Pu, Chuanqiang; Fang, Fang; Shi, Qiang
Abstract: SPG78 is a subtype of hereditary spastic paraplegia(HSP) caused by ATP13A2 gene mutations. SPG78 was reported as complicated HSP in several cases, but was never associated with pure HSP. Here we report the first Chinese patient carrying a novel homozygous nonsense mutation in ATP13A2 presenting with pure HSP.